Violation of freedom of the press : a compendium of adjudications rendered by the Press Council of India - Loghani, Usha; Press Council of India; Indian Law Institute (Bombay : N.M. Tripathi, 1986)
Digest of cases.
'Under the joint auspices of the Press Council of India & the Indian Law Institute.'
Includes bibliographical references and index.
Keywords: Press law -- India -- Cases; Journalistic ethics -- India -- Cases; Freedom of the press -- India -- Cases